PENERAPAN KONSEP EKONOMI KREATIF PADA KOMUNITAS LOKAL UNTUK PENGEMBANGAN PARIWISATA BERKELANJUTAN - I Made Marthana Yusa; Melyana R Pugu; Azy Athoillah Yazid; Al-Amin (JOURNAL OF COMMUNITY DEDICATION, 2025)
The purpose of this research is to see how Application of the Creative Economy Concept to Local Communities for Sustainable Tourism Development. The method of this research is This research is a type of literature research; This means that the information materials used come from library sources in the form of books, encyclopedias, magazines, journals, newspapers, journals, and others. The form of this research is descriptive, analytical, and critical. The application of the green economy concept in the local agricultural sector can have a positive impact on increasing productivity, especially with an approach that focuses on sustainability and wise management of natural resources. By involving the community in the development of creativity-based products, as well as introducing educational and environmentally friendly tourism, local communities can become the main actors in creating tourism that is not only economically beneficial, but also socially and ecologically responsible. However, challenges such as access to capital, infrastructure, and managerial knowledge need to be addressed with support from governments, the private sector, and educational institutions to ensure that the creative economy can develop sustainably in context.